2023
DOI: 10.3389/fimmu.2023.1180209
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer associated CD169+ macrophages possess broad immunosuppressive functions but enhance antibody secretion by activated B cells

Frida Björk Gunnarsdottir,
Oscar Briem,
Aida Yifter Lindgren
et al.

Abstract: CD169+ resident macrophages in lymph nodes of breast cancer patients are for unknown reasons associated with a beneficial prognosis. This contrasts CD169+ macrophages present in primary breast tumors (CD169+ TAMs), that correlate with a worse prognosis. We recently showed that these CD169+ TAMs were associated with tertiary lymphoid structures (TLSs) and Tregs in breast cancer. Here, we show that CD169+ TAMs can be monocyte-derived and express a unique mediator profile characterized by type I IFNs, CXCL10, PGE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…A recent study revealed that CD169+TAMs colocalize with T cells (along with regulatory T cells) in human breast tumors, and suppress T cells and NK cells, possibly via the release of PGE2, ROS and IL-1. 40 It is not known whether CD169+PV TAMs do so in ADT-treated tumors and whether this contributes to the resistance of primary tumors to ADT. Interestingly, a recent study showed that CD169+macrophages promote resistance to the anti-androgen, enzalutamide (an AR antagonist) in mouse (prostate) bone metastases.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study revealed that CD169+TAMs colocalize with T cells (along with regulatory T cells) in human breast tumors, and suppress T cells and NK cells, possibly via the release of PGE2, ROS and IL-1. 40 It is not known whether CD169+PV TAMs do so in ADT-treated tumors and whether this contributes to the resistance of primary tumors to ADT. Interestingly, a recent study showed that CD169+macrophages promote resistance to the anti-androgen, enzalutamide (an AR antagonist) in mouse (prostate) bone metastases.…”
Section: Discussionmentioning
confidence: 99%